Mesenchymal and stemness transdifferentiation via in-vitro infection of T24 cell line with Klebsiella pneumoniae (Baghdad Science Journal, 2023)
Klebsiella pneumoniae has been found in the urinary tract of some bladder cancer patients. Bacterial presence within tumor tissue may affect the tumor-microenvironment and consequently influence cancer behavior, development, and treatment response. This study investigated mesenchymal and stemness transdifferentiation of bladder cancer cell line due to environmental stress of K. pneumoniae. Cultures of urothelial bladder cancer cell line (T24) were infected with K. pneumoniae with different multiplicity of infection (MOI) for two and four days. Transdifferentiation-associated features were morphologically assessed.Moreover, transdifferentiation markers were estimated using Q-PCR and immunohistochemistry. Q-PCR data showed an increase in mesenchymal transdifferentiation traits; vimentin expression was upregulated, and cytokeratin19 expression downregulated significantly (P<0.001) compared with controls, which were emphasized by immunohistochemistry results. Moreover, stemness transdifferentiation markers expression increased significantly (P<0.001). The heterogeneous tumor cell population may be altered by bacterial infection, which improves cancer cells' migration and self-renewal ability. Thus, bacteria may be engaged in cancer progression and metastases.